2022
DOI: 10.1097/md.0000000000029643
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gallbladder polyps observed through second-look abdominal sonography in patients with fatty liver disease

Abstract: Multiple studies have provided varied results on the relationship between gallbladder polyps (GBPs), fatty liver disease (FLD), and metabolic factors.The purpose of this study was to determine the possible risk factors related to GBP formation in Taiwanese population through the use of health examinations.In this retrospective study, 1311 subjects who underwent abdominal sonography for health evaluations from September 2019 to August 2020 were randomly enrolled. Baseline characteristics of the study subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Thus, they stressed that plain abdominal preoperative US alone may not be reliable for diagnosing GB polyps. [62] Similar allegations for the reliability of US alone have been formulated by Lodhi et al, who recommend following MRI. [25] It has been reported that GB polyps may be detected on US during a second look in cases of fatty liver disease, older age and alcohol consumption, where there are imaging difficulties.…”
Section: Diagnosismentioning
confidence: 81%
“…Thus, they stressed that plain abdominal preoperative US alone may not be reliable for diagnosing GB polyps. [62] Similar allegations for the reliability of US alone have been formulated by Lodhi et al, who recommend following MRI. [25] It has been reported that GB polyps may be detected on US during a second look in cases of fatty liver disease, older age and alcohol consumption, where there are imaging difficulties.…”
Section: Diagnosismentioning
confidence: 81%
“…Blood alcohol stimulates cholecystokinin secretion in the pancreas, counteracting cholesterol GBP formation by increasing gallbladder motility [16,17]. However, a Taiwanese group demonstrated alcohol consumption to be an independent risk factor for GBP [18].…”
Section: Introductionmentioning
confidence: 99%
“…Blood alcohol stimulates cholecystokinin secretion in the pancreas, counteracting cholesterol GBP formation by increasing gallbladder motility [16,17]. However, a Taiwanese group demonstrated alcohol consumption to be an independent risk factor for GBP [18]. Well-known risk factors for GBP development and progression include the male sex, age, dyslipidemia, and non-alcoholic fatty liver disease [1,8,9].…”
Section: Introductionmentioning
confidence: 99%